FUTURE DIRECTIONS OF THE CURRENT TOCOLYTIC THERAPY AS A PART OF COMBINATION THERAPY FOR THREATENED PRETERM LABOR (LITERATURE SURVEY) - Y. E. Dobrochotova; A. V. Van; A. S. Culicova (Акушерство, гинекология и репродукция)
An analysis of literature data is given regarding the role of different types of therapy used for the treatment of threatened preterm labor including the efficacy and safety of such treatments.